2013
DOI: 10.4236/ojgas.2013.34040
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hepatitis B infection and factors associated in children of Ivorian HBsAg carrier subjects

Abstract: Aims of the Study: 1) Determine the Prevalence of Hepatitis B virus (HBV) infection in children (contact subjects) of chronic Hepatitis B surface antigen (HBsAg) carrier subjects (index subjects); 2) Search for factors associated with HBV infection in these children. Patients and Methods: Retrospective-crosssectional study (January 5th, 2006 through December 31st, 2012). Studied parameters: biological and clinical characteristics of index subjects; Prevalence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…The average age of our patients was 49.2 years. They were 42.3 years old for VHB which is consistent with other studies carried out in Côte d'Ivoire that found an average age of 42 years for chronic carriers of HBs Ag [9] and 40 [10], in France HBV patients had a median age of 44 years [11]. Our HCV patients were on average 51.9 years old, in line with SOMBIE et al who found an average age of 51 ± 6.9 years in HCV patients put on treatment [6] and a study in Morocco where HCV patients were on average 52 years old [12], in Tunisia the average age of HCV patients was 50 years [13] and 53.1 ± 8.1 years in Cameroon [7].…”
Section: Discussionsupporting
confidence: 91%
“…The average age of our patients was 49.2 years. They were 42.3 years old for VHB which is consistent with other studies carried out in Côte d'Ivoire that found an average age of 42 years for chronic carriers of HBs Ag [9] and 40 [10], in France HBV patients had a median age of 44 years [11]. Our HCV patients were on average 51.9 years old, in line with SOMBIE et al who found an average age of 51 ± 6.9 years in HCV patients put on treatment [6] and a study in Morocco where HCV patients were on average 52 years old [12], in Tunisia the average age of HCV patients was 50 years [13] and 53.1 ± 8.1 years in Cameroon [7].…”
Section: Discussionsupporting
confidence: 91%
“…Earlier [40][41][42] and recent reports [43][44][45][46][47] from Nigeria and studies from Ghana [36], Sierra Leone [37], Cameroon [38], and Cote D'viore [39] showed age-related increase in prevalence of HBsAg.…”
Section: Discussionmentioning
confidence: 98%
“…However recent studies of Hepatitis B in different children's populations in the West African sub-region reported prevalence of 12.3% in Ghana [36], 13.7% in Sierra Leone [37], 20.5% in Cameroon [38] and 4% in Cote Dviore [39]. These reports had small sample sizes, limited sex and age ranges and short study duration, but contributory to HBV epidemiology in the region.…”
Section: Discussionmentioning
confidence: 99%